LUARAN PASIEN STROKE ISKEMIK AKUT DENGAN INFEKSI COVID-19 DI JAKARTA - Wiwit Ida Chahyani; Murni Sri Hastuti; Malika Malika; Izati Rahmi; Maria Regina Rachmawati; Anwar Wardy Warongan (alm); Siti Airiza Ahmad (PERDOSNI, 2022)
ABSTRACT Introduction: Ischemic stroke is a life-threatening neurological complication of coronavirus disease 19 (COVID-19). Research on the outcome of acute ischemic stroke patients with COVID-19 infection in Indonesia has not been widely reported. Aims: We investigated the outcome of acute ischemic stroke patients with COVID-19 infection and the factors that affect these outcomes at the Pasar Minggu Regional General Hospital, which is a special COVID-19 referral hospital in Jakarta, Indonesia. Methods: This was a cross sectional study based on the medical records of acute ischemic stroke patients with laboratory-confirmed COVID-19 infection of those ≥18 years of age, who were hospitalized at the Pasar Minggu Regional General Hospital between March 2020 and June 2021. Chi-squared test and unpaired t-test were used for statistical analyses. Results: Thirty-six patients were included in the study. The majority were ≥50 years old (69.4%), comprising of 58.3% women, and 52.8% revealed National Institute of Health Stroke Scale (NIHSS) score of ≤5. The mortality rate of acute ischemic stroke patients with COVID-19 infection was 16.7%, and in the survivors, the median modified Rankin scale score at discharge was 2(1–5). There was a significant association between the severity of COVID-19 and mortality in acute ischemic stroke patients infected with COVID-19 (P=0.019; Odds ratio 1.5 [95% confidence interval 1.08-2.08]). Discussion: The mortality of acute ischemic stroke patients with COVID-19 infection was high, and the factor of significant influence was COVID-19 disease severity. The majority of acute ischemic stroke patients with COVID-19 who survived had mild disabilities.Keywords: COVID-19, ischemic stroke, outcome.